A novel peer-to-peer congestion pricing marketplace enabled by vehicle-automation. (December 2016) - Le Vine, Scott; Polak, John
Highlights: We propose a novel peer-to-peer system for trading positions in a traffic stream. The system requires participating vehicles to be under automated operation. The system is voluntary and does not require all vehicles to take part. We expose the system's properties, but do not take a view of whether it is good or bad. Abstract: This paper proposes a novel concept of congestion pricing based on voluntary peer-to-peer exchange of money between motorists in exchange for one ceding priority to another in a traffic stream. While in the classical congestion charging paradigm payments are compulsory and flow only towards the system operator, in the proposed marketplace participation is voluntary and motorists directly compensate each other. A particular motorist may find that he/she is a 'payer' at certain points in a given journey and a 'payee' at others. Humans would not be expected to successfully seek, negotiate and execute a continuous series of peer-to-peer trades involving micro-payments while also handling the cognitively-demanding task of driving; real-world implementation will therefore require vehicles operating under fully-automated control in both the longitudinal and lateral dimensions during the time periods that they seek and engage in trades. The automated vehicle control algorithms must be sufficiently intelligent and adaptable to enable alternative maneuvers on short timescales, given the inherent uncertainty of whether or not a potential trade will in fact be executed. The peer-to-peer trading would be executed algorithmically, subject to strategic-level guidance given by a vehicle's occupant(s) regarding the occupant's relative valuation of money and priority in the traffic stream. In this paper we detail the prospective marketplace and present a simple simulation model to expose its properties. We show that the proposed peer-to-peer marketplace could lead to both desirable and undesirable outcomes; which of these would be predominant is a matter requiring empirical study. The paper concludes with a discussion of further research needs to refine and develop these concepts into practice.